Gambaran Perilaku Masyarakat tentang Upaya Pencegahan Penyakit Demam Berdarah Dengue - Bellinda Putri Kolondam; Jeini Ester Nelwan; Grace Debbie Kandou (Indonesian Journal of Public Health and Community Medicine, 2020)
Dengue Hemorrhagic Fever is an infectious disease caused by the Dengue virus and transmitted through the Aedes aegypti mosquito. In 2019 the number of cases recorded at the MinangaÂ  Health Center in Manado City was cases with 16 cases occurring in Malalayang Kelurahan 1, so that efforts were needed to prevent DHF. The purpose of this study was to determine the picture of knowledge, attitudes, and actions regarding dengue prevention efforts. Quantitative is the research design used in this study. The study was conducted for two months, starting from September and ending in October 2019 in the Malalayang 1. The population in this study was the entire community which numbered 2,662 families and the study sample was 163 respondents. The instrument used in this study was a questionnaire, then the data in this study were processed using SPSS.Univariate analysis found that the majority of respondents had a good level of knowledge (59.5%) with most having high school education (54.6%). Attitude level obtained by most of the respondents fall in the good category (83.4%) and as for behavior most respondents' actions included in the less category (56.5%). The conclusion of this study shows that Knowledge of Attitudes and Actions influences efforts to prevent dengue fever